2014
DOI: 10.3324/haematol.2013.098517
|View full text |Cite
|
Sign up to set email alerts
|

t(6;9)(p22;q34)/DEK-NUP214-rearranged pediatric myeloid leukemia: an international study of 62 patients

Abstract: IntroductionThe t(6;9)(p22;q34), frequently reported with a breakpoint in 6p23 but now known to involve the DEK gene mapping to 6p22.3, is a rare translocation, estimated to occur in 1-2% of cases of childhood acute myeloid leukemia (AML). 1 The translocation was first identified in 1976, and the first pediatric patient was described in 1982.2,3 The World Health Organization (WHO) classification of myeloid neoplasms and acute leukemia from 2008 listed the t(6;9)(p22;q34) as a distinct entity. 4 However, our cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 42 publications
1
82
1
1
Order By: Relevance
“…Data from two studies have revealed that the expression of DEK-NUP214 may increase the overall protein production by targeting translation [6], and may additionally accelerate proliferation through up-regulation of the mTOR pathway [7]. A recent international multicenter study has concluded that DEK-NUP214 represents a unique subtype of AML accompanied by increased risk of relapse, higher FMS-like tyrosine kinase 3 internal tamdem dulpication (FLT3 ITD) mutation frequency and a defined gene signature [8]. However, the precise molecular function of this fusion gene and its disease contribution remain mostly elusive.…”
Section: Introductionmentioning
confidence: 96%
“…Data from two studies have revealed that the expression of DEK-NUP214 may increase the overall protein production by targeting translation [6], and may additionally accelerate proliferation through up-regulation of the mTOR pathway [7]. A recent international multicenter study has concluded that DEK-NUP214 represents a unique subtype of AML accompanied by increased risk of relapse, higher FMS-like tyrosine kinase 3 internal tamdem dulpication (FLT3 ITD) mutation frequency and a defined gene signature [8]. However, the precise molecular function of this fusion gene and its disease contribution remain mostly elusive.…”
Section: Introductionmentioning
confidence: 96%
“…Nup214, located at the cytoplasmic filament of the NPC, interacts with NTRs to control macromolecular transport. set-nup214 and dek-nup214 have been identified in acute undifferentiated leukemia and acute myeloid leukemia (AML), respectively (16, 17) and have recently been found in several T-cell acute lymphoid leukemia (T-ALL) and AML patients (18,19). SET-Nup214 has been found to bind to the hoxa locus and activate its expression (20).…”
mentioning
confidence: 99%
“…The t(6;9)(p23;q34) has traditionally been associated with poor prognosis, although a recent retrospective study suggests that the outcome for pediatric patients with this translocation may be more similar to that of other childhood AML 66,67 . Patients are generally treated with either chemotherapy or allogeneic hematopoietic stem cell transplantation, with a slightly more favorable prognosis for the latter group 67 .…”
Section: Dek As An Extracellular Proteinmentioning
confidence: 95%
“…However, the specificity of the DEK antibodies used in these studies has been challenged and the concept remains questionable 16,58 The DEK-NUP214 Fusion Gene The (6;9)(p23;q34) chromosomal translocation was originally identified in small subsets of patients with acute myeloid leukemia 63,64 . Recent assessments have estimated that about 1% of all acute myeloid leukemias carry this specific rearrangement [65][66][67] . It is found in both adult and pediatric AML, but the latter form dominates with a mean age of diagnosis of 23 years 66 .…”
Section: Dek As An Extracellular Proteinmentioning
confidence: 99%
See 1 more Smart Citation